Implementasi Nilai-Nilai Al-Qur’an dalam Pelayanan Jamaah Umroh di Safarindo Albarokah Umroh: Studi Living Qur’an Perspektif QS. An-Nahl: 90 - Mery Agustina; Mutiara Fahliza; Ahmad Raihan Lubis; Hamdani Syahputra; Meilani Meilani; Ali Darta (Lembaga Pengembangan Kinerja Dosen, 2024)
This study examines the implementation of Qur’anic values in the services of Umrah pilgrims at Safarindo Albarokah Umroh using a Living Qur’an approach based on QS. An-Nahl: 90. The verse emphasizes three core values: ‘adl (justice), ihsan (excellence), and ita’ dzil qurba (social care), which serve as guiding principles in service management. This research employs a qualitative descriptive method using observation, in-depth interviews, and documentation. The findings show that all three values have been systematically implemented in administrative services, religious guidance, accompaniment in the Holy Land, and post-travel services. The value of ‘adl is reflected in transparent pricing and fair treatment of pilgrims, ihsan is demonstrated through excellent, responsive, and continuous service, while ita’ dzil qurba is realized through social programs such as scholarships for underprivileged pilgrims and special services for elderly and disabled pilgrims. This study concludes that Safarindo Albarokah Umroh integrates Qur’anic values into its operational system, contributing to the development of Living Qur’an studies in Islamic business practices.